Validity and Reliability of The Numeric Rating Scale in Non-Myogenic Low Back Pain Patients - Adha, Faradila Risky; Komalasari, Dwi Rosella (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Pain is the main problem in LBP that can reduce quality of life. Several tools are used to determine the pain, including Numeric Rating Scale (NRS). NRS need validity and reliability to evaluate pain. Objective: To determine the validity and intra-rater and inter-rater reliability of the NRS in Non-Myogenic Low Back Pain patients. Methods: This research was an observational study with a methodological approach using a purposive sampling technique. The total sample were 55 people. Results: The validity of NRS showed well with p<0.001 and r calculated was higher than 0.9 (higher than r table=0.260). SEM value: 0.20 and MDC: 0.55. While, intra-rater and inter-rater reliability of NRS was very high, with Cronbach Alpha and ICC being more than 0.9 and p<0.05. Conclusion: The NRS was valid and reliable in terms of intra-rater and inter-rater for measuring the level of pain in non-myogenic low back pain.